Expressão dos filamentos intermediários no diagnóstico dos tumores mamários de cadelas - Zuccari, D. A. P. C.; Santana, A. E. [UNESP]; Rocha, N.S. [UNESP] (My University, 2002)
Immunohistochemical evaluation was performed to study the histogenesis of canine mammary tumors and to contribute to a better understanding of their classification. Monoclonal antibodies specific for different types of intermediate filaments (cytokeratins, vimentin, α-actin) were used. Epithelial cells stained positively for cytokeratins and their expression was lost as the malignant transformation occurs. Myoepithelial cells stained positively for vimentin and α-actin. In contrast to vimentin, α-actin lost the expression as the cartilaginous or osseous metaplasia occurs. Immunohistochemical evaluation with monoclonal antibodies proved to be efficient for identification of tumor histogenesis.
Expression of intermediate filaments in canine mammary tumors diagnosis
Keywords: Dog; Immunohistochemistry; Mammary tumor; alpha actin; cytokeratin; monoclonal antibody; vimentin; breast tumor; controlled study; dog disease; female; histogenesis; immunohistochemistry; intermediate filament; malignant transformation; myoepithelium cell; nonhuman; protein expression; tumor classification; tumor diagnosis; Canis familiaris